Enrichment of Artemia with synbiotic and its effects on growth nutrient utilization survival and gut microbial communities of larval hybrid catfish (Clarias microstomus × Clarias gariepinus) - Lingoh, Arlene Debbie; Latif, Kamil; Lee, Yih Nin; Abit, Lirong Yu; Sarbini, Shahrul Razid; Mojilis, Miguel Isaiah Vincent; Shamsul Azhar, Fatin Maisarah; Khairul, Sabrina Rancang; Leong, Sui Sien (John Wiley and Sons, 2025)
Artemia (brine shrimp) is a vital live feed in aquaculture, providing essential nutrients during the early developmental stages of aquatic species. This study aimed to evaluate the efficacy of synbiotic-enriched Artemia franciscana as a live feed for hybrid catfish larvae (Clarias microstomus × Clarias gariepinus), using locally isolated probiotics (Enterococcus faecium and Enterococcus faecalis) and the commercial prebiotic inulin. The study was conducted in two phases. In Phase 1, Artemia were enriched for 6 h with four treatments: T1 (E. faecium W01 + inulin), T2 (E. faecalis + inulin), T3 (E. faecium W02 + inulin), and T4 (control and no synbiotics). Bacterial colonization was assessed microscopically and through colony counts at 2, 4, and 6 h post-enrichment. Synbiotic-treated groups (T1–T3) showed significantly higher bacterial retention than the control (T4), with T1 achieving the highest colonization levels (2 h: 6.98 log CFU/g; 4 h: 7.02 log CFU/g; 6 h: 7.10 log CFU/g; p < 0.05). Control values ranged from 5.12 to 5.45 log CFU/g. Microscopy revealed a distinctive red-brown gut coloration in treated Artemia, indicating successful colonization. In Phase 2, hybrid catfish larvae were fed enriched Artemia for 7 days, followed by a subsequent 7-day period transitioned to enriched Artemia and commercial pellet feed. T3 resulted in the highest weight gain (263.14 ± 34.70 mg), length gain (14.38 ± 5.10 mm), specific growth rate (SGR; 19.59 ± 1.17% day−1), and the lowest feed conversion ratio (FCR; 0.10 ± 0.01), all significantly better than other treatments (p < 0.05). Although survival rates did not differ significantly, T3 recorded the highest survival (57.5 ± 3.81%). Forty presumptive lactic acid bacteria (LAB) were isolated from the fish gut, grouped into four main clusters. These results highlight the potential of synbiotic-enriched Artemia to enhance larval growth and gut health, offering an eco-friendly strategy to improve feed efficiency and reduce antibiotic dependance in aquaculture.